State of the California Current Ecosystem in 2021: Winter is coming? - Thompson, Andrew R.; Bjorkstedt, Eric P.; Bograd, Steven J.; Fisher, Jennifer L.; Hazen, Elliott L.; Leising, Andrew; Santora, Jarrod A.; Satterthwaite, Erin V.; Sydeman, William J.; Alksne, Michaela; Auth, Toby D.; Baumann-Pickering, Simone; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill (Euphausia pacifica) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy (Engraulis mordax) were very abundant, while Pacific Sardine (Sardinops sagax) were low. Similar to past La Niñas, market squid (Doryteuthis opalescens) and young of the year (YOY) Pacific Hake (Merluccius pacificus), YOY sanddabs (Citharichthys spp.), and YOY rockfishes (Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia, Mexican lampfish Triphoturus mexicanus) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion (Zalophus californianus) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.